1998
DOI: 10.1159/000030990
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Stored in a New-Generation ContainerDifferences between Plasma and Platelet Additive Solution II

Abstract: Background and Objectives: In order to preserve platelet concentrates (PCs) with high yields, a new polyolefin platelet storage container (PL 2410, 1.3L, Baxter, La Châtre, France) with increased gas permeability in combination with a larger surface area has been developed. The storage capacity was studied with platelets in plasma and platelets additive solution. Materials and Methods: Platelet concentrate pools (PCs) of different yields suspended in either plasma (PCs-PL; n = 30) or PAS II (PCs-PAS; n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 19 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Additionally, the role of the storage medium used must also be taken into account when discussing cell lysis parameters. Studies comparing PAS III to 100% plasma, the storage medium of our study, showed higher levels of CCL5 (RANTES), CXCL4 (PLT factor 4), TGF-β1, and PLT activation markers when PLTs were stored in PAS III [31,35] or PAS II [36] rather than 100% plasma, indicating that suspension in 100% plasma protects PLTs from lysis. WBC-associated cytokines (Th-1/2) IL-2, pg/ml IL-4, pg/ml IL-5, pg/ml IL-10, pg/ml TNF, pg/ml IFN-γ, pg/ml 4.37 ± Although it is well established that the frequency of febrile non-hemolytic transfusion reactions is reduced by prestorage leukoreduction, other transfusion reactions, predominantly allergic, still occur frequently [6][7][8].…”
Section: Discussionmentioning
confidence: 44%
“…Additionally, the role of the storage medium used must also be taken into account when discussing cell lysis parameters. Studies comparing PAS III to 100% plasma, the storage medium of our study, showed higher levels of CCL5 (RANTES), CXCL4 (PLT factor 4), TGF-β1, and PLT activation markers when PLTs were stored in PAS III [31,35] or PAS II [36] rather than 100% plasma, indicating that suspension in 100% plasma protects PLTs from lysis. WBC-associated cytokines (Th-1/2) IL-2, pg/ml IL-4, pg/ml IL-5, pg/ml IL-10, pg/ml TNF, pg/ml IFN-γ, pg/ml 4.37 ± Although it is well established that the frequency of febrile non-hemolytic transfusion reactions is reduced by prestorage leukoreduction, other transfusion reactions, predominantly allergic, still occur frequently [6][7][8].…”
Section: Discussionmentioning
confidence: 44%